Patient satisfaction with nipple‐sparing mastectomy: A prospective study of patient reported outcomes using the BREAST‐Q. Issue 4 (8th July 2016) - Howard, Michael A.; Sisco, Mark; Yao, Katharine; Winchester, David J.; Barrera, Ermilo; Warner, Jeremy; Jaffe, Jennifer; Hulick, Peter; Kuchta, Kristine; Pusic, Andrea L.; Sener, Stephen F.
Abstract : Background and Objectives: The authors sought to study patient‐reported outcomes following nipple‐sparing mastectomy (NSM). Methods: From 2008 to 2011, the BREAST‐Q was administered to women undergoing NSM surgery for cancer treatment or risk‐reduction prior to surgery and at 2 years after completion of reconstruction. The change in score over time and the impact of surgical indication, complication occurrence, and laterality on scores were analyzed. Results: The BREAST‐Q was prospectively administered to 39 women undergoing NSM for cancer treatment (n = 17) or risk‐reduction (RR) (n = 22). At 2 years after operation, median overall satisfaction with breasts was 75 (IQR = 67, 100). There were significant postoperative increases in scores for overall satisfaction with breasts (+8, P  = 0.021) and psychosocial well‐being (+14, P  = 0.003). Postoperatively, RR patients had significantly higher scores for psychosocial wellness, physical impact (chest), and overall satisfaction with outcome compared to cancer treatment patients ( P  < 0.05). Also, increase from preoperative to postoperative psychosocial wellness was higher in the RR compared to cancer treatment patients (+17 vs. +1, P  = 0.043). Complication occurrence did not significantly impact postoperative scores. Conclusions: Following NSM for cancer treatment or RR, patients demonstrated high levels of satisfaction and quality of life as measured by BREAST‐Q. Satisfaction level increased 2 years following operation. J. Surg. Oncol. 2016;114:416–422 . © 2016 Wiley Periodicals, Inc.